INTEGRATION OF NEW SOCIAL PROTECTION MODEL FOR THE POPULATION AT THE COMMUNITY LEVEL - Davtian, Stepan; Yelchiieva, Oksana (Pressing Problems of Public Administration, 2021)
The article deals with issues of creating and integrating a new social protection model at the community level. The main directions of the integrated model of the population social protection system were analyzed: integration of governance, integration of strategies, integration of processes.The article analyzes changes in the system-organizational links of the existing model for provision of social services and the relationship between subjects of the new model of social services provided within the community.Comply with the Law of Ukraine “On Voluntary Association of Territorial Communities”, the quality and accessibility of public services provided in a united territorial community cannot be lower than the same provided before the association.At the same time, the system of providing social services that existed prior to the creation of communities (centralized), when taking into account peculiarities of relations between communities and state authorities, is incapable of ensuring the provision of social services to the community’s residents according to their needs.The purpose of the article is to analyze the integration process of a new social protection model at the community level.There is a need, in conditions of decentralization, to organize effective work on the transfer of powers from executive authorities to communities in the field of the population, social protection, particularly in terms of preventing the reduction of the amount of social services provided to the community residents prior their the association of communities, the training of specialists, the introduction of new models for provision of social services to the population. Implementation of the defined recommendations will enable community leaders and community specialists to create an integrated social protection system for the population, which will promote the obtaining of social services in a qualitative and timely manner thus meeting needs of the community.At present, the processes for integration of the new model of the social protection system for the population in the communities are in progress, therefore further studies in this direction are obvious and expected.